Low-carbon weather-proof decorative material and preparation method thereof

By using microwave-treated engineering waste soil and acidified modified mineral powder, combined with a variety of emulsions and fibers, a stable inorganic-organic macromolecular structure is formed, which solves the problem of poor weather resistance of low-carbon decorative materials, achieves high wear resistance and weather resistance, extends service life, and promotes the reuse of waste soil.

CN119912193APending Publication Date: 2025-05-02SHENZHEN WENKE LANDSCAPE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411887260.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The existing low-carbon decorative materials have poor weather resistance, which affects the beauty and service life of the building.

Method used

Microwave-treated engineering waste soil and acidified modified ore powder are used as the main raw materials, and combined with coupling agent, first emulsion, second emulsion, fibers and curing agents to form a stable inorganic-organic macromolecular structure.

Benefits of technology

It improves the cross-linking, wear resistance and weather resistance of decorative materials, extends the service life of the materials, and realizes the reuse of engineering abandoned soil, reducing urban garbage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005199674120000111
    Figure BDA0005199674120000111
  • Figure BDA0005199674120000121
    Figure BDA0005199674120000121
  • Figure BDA0005199674120000122
    Figure BDA0005199674120000122
Patent Text Reader

Abstract

The invention discloses a low-carbon weather-proof decorative material and a preparation method thereof, and relates to the technical field of building materials. The low-carbon weather-proof decorative material is prepared from the following raw materials: microwave-treated engineering spoil, acid-modified mineral powder, a coupling agent, a macromolecular emulsion, fibers and a curing agent, wherein the mineral powder comprises wollastonite modified by aluminum silicate; the mineral powder comprises wollastonite modified by aluminum silicate; the first emulsion comprises a polyurethane emulsion; the second emulsion comprises at least one of vinyl acetate-acrylic emulsion, pure acrylic emulsion, ethylene-vinyl acetate copolymer emulsion, styrene-acrylic emulsion and vinyl acetate emulsion. According to the technical scheme, the microwave modified engineering spoil and the acid modified mineral powder are adopted as main raw materials, the manufactured decorative material is high in crosslinking degree, low in sample cracking rate and good in weather resistance, the service life of the material is prolonged, waste resources are fully utilized, and the problem that an existing decorative material is poor in weather resistance can be solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a low-carbon weather-resistant decorative material and a preparation method thereof. Background Art

[0002] At present, a new type of environmentally friendly building decoration material has appeared on the market. This decorative material combines the advantages of traditional ceramic tiles and flexible decorative materials. It has the characteristics of light weight, flexibility, strong weather resistance, easy installation, etc., and is suitable for indoor and outdoor wall decoration. This decorative material is usually obtained by molding water-based polymer emulsion with inorganic substances such as cement, soil, quartz sand or mineral powder. Compared with traditional ceramic tiles and most decorative materials that are difficult to degrade, this decorative material can be completely recycled and processed into new products or restored to ordinary sand and soil after a certain number of years of use, or when its style or color needs to be updated, it meets the requirements of returning to nature. It is a low-carbon and environmentally friendly decorative material for the reuse of construction waste and has a wide range of promotion value.

[0003] In recent years, more and more decorative materials are made of urban waste as raw materials. Most of these decorative materials made of waste as the main material have a single color, not rich in style, and poor weather resistance. These problems not only affect the beauty of the building, but also reduce the service life of the building. Therefore, it is of great significance to develop a low-carbon decorative material with good weather resistance in the field of building decoration materials. Summary of the invention

[0004] The main purpose of the present invention is to provide a low-carbon weather-resistant decorative material and a preparation method thereof, aiming to solve the problem of poor weather resistance of existing low-carbon decorative materials.

[0005] To achieve the above object, the present invention provides a low-carbon weather-resistant decorative material, which comprises the following raw materials by weight: 100 parts of microwave-treated engineering waste soil, 50-300 parts of acid-modified mineral powder, 2-8 parts of coupling agent, 10-25 parts of first emulsion, 20-70 parts of second emulsion, 2-16 parts of fiber, and 0.1-4 parts of curing agent;

[0006] Wherein, the mineral powder comprises wollastonite modified with aluminum silicate;

[0007] The first emulsion includes a polyurethane emulsion;

[0008] The second emulsion includes at least one of vinyl acetate emulsion, pure acrylic emulsion, ethylene-vinyl acetate copolymer emulsion, styrene acrylic emulsion and vinyl acetate emulsion.

[0009] In one embodiment, the acid in the acid-modified mineral powder includes at least one of oxalic acid, carbonic acid, hydrochloric acid and nitric acid; and / or,

[0010] The wollastonite modified with aluminum silicate is prepared by adding stearic acid, titanate coupling agent, aluminum sulfate and sodium silicate to wollastonite; and / or,

[0011] The mineral powder further comprises at least one of corundum, quartz powder, sericite and silicon powder, and in the mineral powder, the mass fraction of wollastonite modified with aluminum silicate is 10-20%; and / or,

[0012] The coupling agent includes at least one of a methacryloyloxyalkyl coupling agent, an epoxyhydroxyl coupling agent and an aminohydroxyl coupling agent; and / or,

[0013] The fiber comprises at least one of glass fiber, carbon fiber, brucite fiber and wollastonite fiber; and / or,

[0014] The curing agent includes any one of a polyamide curing agent, an aziridine curing agent and a polycarbodiimide curing agent.

[0015] In one embodiment, the low-carbon weather-resistant decorative material further comprises 5 to 20 parts of a resin, wherein the resin comprises at least one of a phenolic resin, an epoxy resin, a bismaleimide resin, a cyanate resin and a polyimide resin.

[0016] In one embodiment, the low-carbon weather-resistant decorative material further comprises 1.5 to 5 parts of aluminum sol.

[0017] The present invention provides a method for preparing the low-carbon weather-resistant decorative material, comprising the following steps:

[0018] S10, mixing the microwave-treated engineering waste soil, acid-modified mineral powder and water to obtain a mixture;

[0019] S20, mixing the mixture and the coupling agent, and heating to obtain a modified mixture;

[0020] S30, mixing the modified mixture, the first emulsion, the second emulsion, the fiber and the curing agent to obtain a slurry;

[0021] S40, pouring the slurry into a mold, drying, demoulding, and obtaining the low-carbon weather-resistant decorative material.

[0022] In one embodiment, before step S10, the following steps are included:

[0023] Performing microwave treatment on engineering waste to obtain microwave-treated engineering waste; mixing mineral powder and acid to obtain acid-modified mineral powder;

[0024] Wherein, the mass ratio of the mineral powder to the acid is (50-300):(1-5).

[0025] In one embodiment, in step S20, the heating temperature is 60-100°C.

[0026] In one embodiment, in step S40, the drying temperature is 60-130°C.

[0027] In one embodiment, the step S30 includes:

[0028] mixing water and an auxiliary agent to obtain a first mixture;

[0029] The first emulsion, the second emulsion, the modified mixed material, the fiber and the curing agent are added to the first mixture to obtain a slurry.

[0030] In one embodiment, the step S30 includes:

[0031] mixing the first emulsion, the second emulsion, the resin, water, the additive, the fiber and the curing agent to obtain a second mixture;

[0032] The second mixture is added to the modified mixture to obtain a slurry.

[0033] In one embodiment, the step S30 includes:

[0034] mixing the first emulsion, the second emulsion, aluminum sol, water, an additive, fiber and a curing agent to obtain a third mixture;

[0035] The third mixture is added to the modified mixture to obtain a slurry.

[0036] The technical solution of the present invention uses microwave-modified engineering spoil and acid-modified mineral powder as main raw materials, and forms a stable inorganic-organic macromolecular structure under the joint action of a coupling agent, a first emulsion, a second emulsion, fibers and a curing agent. The microwave-modified engineering spoil and the acid-modified mineral powder are used as raw materials to overcome the defects of poor weather resistance of using only engineering spoil or high cost of using only mineral powder; microwave treatment of engineering spoil and acid modification of mineral powder improve the activity of engineering spoil and mineral powder; wollastonite modified with aluminum silicate can enhance the performance of inorganic materials. The interface bonding ability between the material and the organic material; the first emulsion can enhance the mechanical strength and wear resistance of the material; the second emulsion can enhance the bonding effect of each raw material, and the two emulsions are used at the same time. The second emulsion is used as the basis, and the first emulsion with multiple glass transition temperatures is introduced, so that the second emulsion can have a larger difference in temperature adaptability, and can better adapt to a wide range of temperature changes, which is conducive to improving the weather resistance of soft porcelain. Therefore, the decorative material provided by the technical solution of the present invention has a high degree of cross-linking, good wear resistance, good weather resistance, and a long service life of the material, which can be used to solve the problem of poor weather resistance of existing decorative materials. In addition, the technical solution of this application reuses engineering waste soil, realizes the transformation of engineering waste soil into treasure, and can reduce urban garbage. DETAILED DESCRIPTION

[0037] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] It should be noted that if the embodiments of the present invention involve directional indications (such as up, down, left, right, front, back, etc.), the directional indications are only used to explain the relative position relationship, movement status, etc. between the components in a certain specific posture. If the specific posture changes, the directional indication will also change accordingly.

[0039] In addition, if there are descriptions involving "first", "second", etc. in the embodiments of the present invention, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of technical features indicated. Therefore, the features limited to "first" and "second" may explicitly or implicitly include at least one of the features. In addition, if "and / or" or "and / or" appears in the full text, its meaning includes three parallel solutions. Taking "A and / or B" as an example, it includes solution A, solution B, or solutions that satisfy both A and B. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in this field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0040] At present, a new type of environmentally friendly building decoration material has appeared on the market. This decorative material combines the advantages of traditional ceramic tiles and flexible decorative materials. It has the characteristics of light weight, flexibility, strong weather resistance, easy installation, etc., and is suitable for indoor and outdoor wall decoration. This decorative material is usually obtained by molding water-based polymer emulsion with inorganic substances such as cement, soil, quartz sand or mineral powder. Compared with traditional ceramic tiles and most decorative materials that are difficult to degrade, this decorative material can be completely recycled and processed into new products or restored to ordinary sand and soil after a certain number of years of use, or when its style or color needs to be updated, it meets the requirements of returning to nature. It is a low-carbon and environmentally friendly decorative material for the reuse of construction waste and has a wide range of promotion value.

[0041] In recent years, more and more decorative materials are made of urban waste as raw materials through roller forming. The direct use of untreated waste will lead to poor organic-inorganic crosslinking effect, poor weather resistance, easy fading, easy breakage and ugly style of the prepared decorative materials. Moreover, most of the low-carbon weather-resistant decorative materials made of waste as the main material have a single color and insufficient style. These problems not only affect the beauty of the building, but also reduce the service life of the building. Therefore, it is of great significance to develop a low-carbon weather-resistant decorative material with good weather resistance in the field of building decoration materials.

[0042] At present, the ingredients of low-carbon decorative materials are either all waste materials or all mineral raw materials. The low-carbon weather-resistant decorative materials made of waste materials are ugly in style, single in color, greatly affected by the color of the raw materials themselves, and have the disadvantage of poor weather resistance. These problems not only affect the beauty of the building, but also reduce the service life of the building; the use of all mineral raw materials is costly and does not conform to the current concept of energy conservation, emission reduction, green and low carbon. Therefore, it is of great significance to develop a low-carbon decorative material with good weather resistance in the field of building decoration materials.

[0043] In view of this, the present invention proposes a low-carbon weather-resistant decorative material, comprising the following raw materials by weight: 100 parts of microwave-treated engineering waste soil, 50-300 parts of acid-modified mineral powder, 2-8 parts of coupling agent, 10-25 parts of first emulsion, 20-70 parts of second emulsion, 2-16 parts of fiber, and 0.1-4 parts of curing agent;

[0044] Wherein, the mineral powder comprises wollastonite modified with aluminum silicate;

[0045] The first emulsion includes a polyurethane emulsion;

[0046] The second emulsion includes at least one of vinyl acetate emulsion, pure acrylic emulsion, ethylene-vinyl acetate copolymer emulsion, styrene acrylic emulsion and vinyl acetate emulsion.

[0047] The technical solution of the present invention uses microwave-modified engineering spoil and acid-modified mineral powder as main raw materials, and forms a stable inorganic-organic macromolecular structure under the joint action of a coupling agent, a first emulsion, a second emulsion, fibers and a curing agent. The microwave-modified engineering spoil and the acid-modified mineral powder are used as raw materials together, which overcomes the defects of poor weather resistance of using only engineering spoil or high cost of using only mineral powder; microwave treatment of engineering spoil and acid modification of mineral powder improve the activity of engineering spoil and mineral powder; wollastonite modified with aluminum silicate can enhance the performance of inorganic materials and organic The interface bonding ability between organic materials; the first emulsion can enhance the mechanical strength and wear resistance of the material; the second emulsion has good bonding performance, which can enhance the bonding effect of each raw material. Using two emulsions at the same time, using the second emulsion as the basis, introducing the first emulsion with multiple glass transition temperatures, the second emulsion can have a larger temperature adaptability difference, can better adapt to a wide range of temperature changes, and is conducive to improving the weather resistance of soft porcelain. Therefore, the decorative material provided by the technical solution of the present invention has a high degree of cross-linking, good wear resistance, good weather resistance, and a long service life of the material, which can be used to solve the problem of poor weather resistance of existing decorative materials. In addition, the technical solution of this application reuses engineering waste soil, realizes the transformation of engineering waste soil into treasure, and can reduce urban garbage.

[0048] It should be noted that untreated engineering waste soil cannot be used directly. Direct use will lead to poor organic-inorganic cross-linking effect, poor weather resistance, and easy fading. Microwave treatment uses the characteristics of engineering waste soil under microwave high temperature pyrolysis effect to activate and heat the organic molecules and water molecules in the engineering waste soil, which is conducive to accelerating the chemical reaction process; acid-modified mineral powder is to acidify the mineral powder to form ionic bonds on the surface of the mineral powder. The ionic bonds play the role of connecting nodes, which is conducive to forming a stable inorganic macromolecular structure and improving Weather resistance of the material: Wollastonite is a heterogeneous silicate filler, which can reduce volume shrinkage during the drying process of the material and improve the product's resistance to cracking and scrubbing. Compared with unmodified wollastonite, wollastonite modified with aluminum silicate has nanoparticles coated on the surface of wollastonite, thereby retaining the strength of wollastonite rigid particles and enhancing the interfacial bonding ability between inorganic and organic materials. The weather resistance of the low-carbon weather-resistant decorative material prepared by using two emulsions at the same time is better than that of the low-carbon weather-resistant decorative material prepared by using the first emulsion alone or the second emulsion alone.

[0049] The present invention does not limit the source of the engineering waste soil. In the embodiment of the present invention, the engineering waste soil comes from engineering waste somewhere in Longgang District, Shenzhen.

[0050] In the embodiment of the present invention, the power of the microwave treatment is 700-1000W, and the time of the microwave treatment is 5-15min. Microwave treatment of engineering spoil can activate and heat the organic molecules and water molecules in the engineering spoil, which is conducive to accelerating subsequent chemical reactions. Before microwave treatment, the engineering spoil can also be crushed, ball-milled, and sieved, which is conducive to improving the activity of the engineering spoil.

[0051] In an embodiment of the present invention, the acid in the acid-modified mineral powder includes at least one of oxalic acid, carbonic acid, hydrochloric acid and nitric acid. The mineral powder is treated with acid to form ionic bonds on the surface of the mineral powder. The ionic bonds play the role of connecting nodes. By forming complexes with ligands, these complexes can serve as "bridges" to connect different mineral powder particles, thereby facilitating the formation of a stable inorganic macromolecular structure and facilitating the preparation of a decorative material with a high degree of cross-linking and good weather resistance. In one embodiment of the present invention, oxalic acid is selected to acidify the mineral powder.

[0052] In an embodiment of the present invention, the wollastonite modified with aluminum silicate is prepared by adding aluminum sulfate, sodium silicate, stearic acid and a titanate coupling agent to wollastonite. In one embodiment of the present invention, the specific preparation steps of the wollastonite modified with aluminum silicate are as follows:

[0053] Pour wollastonite powder into water and stir at a speed of 300-400r / min. After stirring into a uniformly dispersed suspension, test the pH value. If the pH value is not 7, adjust the pH value to 7 with ammonia water or sodium bicarbonate. Subsequently, when the temperature of the suspension is raised to 80°C, add aluminum sulfate and sodium silicate solution, continue stirring for 30 minutes after the dropwise addition, filter, wash, filter again, dry in an oven at 105°C, and then break up to obtain a powder. After the obtained powder is fully mixed with stearic acid and titanate coupling agent, aluminum silicate-modified wollastonite is obtained.

[0054] In an embodiment of the present invention, the mineral powder further comprises at least one of corundum, quartz powder, sericite and silica powder, and the mass fraction of wollastonite modified with aluminum silicate in the mineral powder is 10-20%. Corundum can significantly improve the hardness and wear resistance of the material, and improve the high temperature resistance of the prepared decorative material; quartz powder can enhance the mechanical strength, chemical stability and corrosion resistance of the material, and reduce the risk of cracking; an appropriate amount of sericite can reduce the degree of cracking and improve the durability of the decorative material; silica powder can improve the density of building materials, improve the fire resistance, enhance the internal bonding of soft porcelain, better combine with other components, and improve the overall mechanical properties.

[0055] The mineral powder further includes at least one of corundum, quartz powder, sericite and silica powder, which means that the mineral powder can be any one of corundum, quartz powder, sericite and silica powder and wollastonite modified with aluminum silicate, or a combination of two or more of corundum, quartz powder, sericite and silica powder and wollastonite modified with aluminum silicate. Preferably, the mineral powder includes corundum, quartz powder, sericite, silica powder and wollastonite modified with aluminum silicate.

[0056] In an embodiment of the present invention, the coupling agent includes at least one of a methacryloyloxyalkyl coupling agent, an epoxyhydroxyl coupling agent, and an aminohydroxyl coupling agent. The coupling agent is used to improve the interfacial compatibility and bonding force between the inorganic filler and the organic matrix. The silane coupling agent can undergo a hydrolysis reaction with a small amount of water and an auxiliary agent, and generate a silane oligomer after dehydration condensation; the silane oligomer reacts with the hydroxyl groups on the surface of the engineering spoil or the mineral powder, and dehydration condensation generates a silicon-oxygen bond; after being added to the emulsion, the functional groups on the surface of the engineering spoil and the functional groups on the surface of the mineral powder react with the functional end groups in the emulsion to form valence bond crosslinking, and finally generate a hybrid material with a network chain structure.

[0057] In an embodiment of the present invention, the fiber includes at least one of glass fiber, carbon fiber, brucite fiber and wollastonite fiber. Glass fiber can improve and enhance the physical and mechanical properties of the material. Carbon fiber has extremely high tensile strength and elastic modulus, which helps to improve the mechanical strength and rigidity of the prepared decorative material. Brucite fiber and wollastonite fiber can reduce the adsorption phenomenon of the surface energy of the material, form an interface effect zone with strong bonding force, and give the material a higher structural strength.

[0058] In an embodiment of the present invention, the curing agent includes any one of polyamides, isopropionate, formaldehyde, aziridine, and polycarbodiimide. The curing agent can accelerate the cross-linking process between polymer chains, so that the material changes from a liquid or semi-solid state to a solid state, and improves the mechanical properties of the material, such as hardness, strength, and chemical resistance. The curing agent of the technical solution of the present invention is a water-based curing agent, and the water-based curing agent is used to participate in the cross-linking and curing of the aqueous emulsion, which can improve the heat resistance, wear resistance, and mechanical strength of the material.

[0059] In an embodiment of the present invention, the low-carbon weather-resistant decorative material further comprises 0.2 to 6 parts of an auxiliary agent, wherein the auxiliary agent comprises at least one of a thickener, a dispersant and a defoaming agent.

[0060] In an embodiment of the present invention, in the untreated mineral powder, the low-carbon weather-resistant decorative material further comprises 5 to 20 parts of resin, wherein the resin comprises at least one of phenolic resin, epoxy resin, bismaleimide resin, cyanate resin and polyimide resin. An appropriate amount of resin helps to increase the viscosity of the emulsion and improve the corrosion resistance of the emulsion.

[0061] In an embodiment of the present invention, in the untreated mineral powder, the low-carbon weather-resistant decorative material further comprises 1.5 to 5 parts of aluminum sol. The technical solution of the present invention selects aluminum sol with a particle size of 60 to 80 nm. The introduction of nano aluminum sol can reduce the pores on the surface of the material, enhance its compactness, reduce its water permeability, and improve the hardness of the resin material, thereby improving the hardness of the low-carbon weather-resistant decorative material.

[0062] The present invention provides a method for preparing the low-carbon weather-resistant decorative material, comprising the following steps:

[0063] S10, mixing the microwave-treated engineering waste soil, acid-modified mineral powder and water to obtain a mixture;

[0064] S20, mixing the mixture and the coupling agent, and heating to obtain a modified mixture;

[0065] S30, mixing the modified mixture, the first emulsion, the second emulsion, the fiber and the curing agent to obtain a slurry;

[0066] S40, pouring the slurry into a mold, drying, demoulding, and obtaining the low-carbon weather-resistant decorative material.

[0067] In the present invention, microwave-modified engineering spoil and acid-modified mineral powder are first mixed, and then a silane coupling agent is added for modification to improve the compatibility between the microwave-modified engineering spoil and the acid-modified mineral powder, and then other raw materials are added to form a stable inorganic-organic macromolecular structure to obtain the low-carbon weather-resistant decorative material. The silane coupling agent is used to undergo a hydrolysis reaction with a small amount of water and an auxiliary agent, and dehydration condensation is performed to generate a silane oligomer; the silane oligomer reacts with the surface hydroxyl groups of the engineering spoil or the mineral powder, and dehydration condensation is performed to generate a silicon-oxygen bond. After the emulsion is added, the functional groups on the surface of the engineering spoil and the functional groups on the surface of the mineral powder react with the functional end groups in the emulsion to form valence bond crosslinking, and finally a hybrid material with a network chain structure is generated.

[0068] In an embodiment of the present invention, before step S10, the following steps are included:

[0069] Performing microwave treatment on engineering waste to obtain microwave-treated engineering waste; mixing mineral powder and acid to obtain mineral powder modified with inorganic acid;

[0070] Wherein, the mass ratio of the mineral powder to the acid is (50-300):(1-5).

[0071] In an embodiment of the present invention, in step S20, the heating temperature is 60-100° C. Heating can promote the hydrolysis and condensation reaction of the coupling agent and the reaction between the coupling agent and the surface of the mineral powder. At this temperature, the coupling effect of the coupling agent is better.

[0072] In an embodiment of the present invention, in step S40, the drying temperature is 60-130° C. Setting the drying temperature within the above range can balance the drying speed and the removal of moisture inside the material, avoiding the generation of surface stress and internal defects. Preferably, the drying temperature is 60-90° C.

[0073] In an embodiment of the present invention, step S30 includes:

[0074] mixing water and an auxiliary agent to obtain a first mixture;

[0075] The first emulsion, the second emulsion, the modified mixed material, the fiber and the curing agent are added to the first mixture to obtain a slurry.

[0076] It should be noted that in order to evenly disperse the additives and enable each raw material to better play a modifying role, the technical solution of the present invention selects to first mix water and additives, and then add the first emulsion, the second emulsion, the modified mixture, the fiber and the curing agent.

[0077] In an embodiment of the present invention, step S30 includes:

[0078] mixing the first emulsion, the second emulsion, the resin, water, the additive, the fiber and the curing agent to obtain a second mixture;

[0079] The second mixture is added to the modified mixture to obtain a slurry.

[0080] It should be noted that, in order to evenly disperse the additives and enable each raw material to better play a modifying role, the technical solution of the present invention selects to mix the first emulsion, the second emulsion, the resin, water, the additives, the fiber and the curing agent, and then add the resulting mixture to the modified mixture. Among them, adding an appropriate amount of resin helps to increase the viscosity of the emulsion and improve the corrosion resistance of the emulsion.

[0081] In an embodiment of the present invention, step S30 includes:

[0082] mixing the first emulsion, the second emulsion, aluminum sol, water, an additive, fiber and a curing agent to obtain a third mixture;

[0083] The third mixture is added to the modified mixture to obtain a slurry.

[0084] It should be noted that, in order to evenly disperse the additives and enable each raw material to better play a modifying role, the technical solution of the present invention mixes the first emulsion, the second emulsion, the aluminum sol, water, the additives, the fiber and the curing agent, and then adds the resulting mixture to the modified mixture. Among them, adding an appropriate amount of aluminum sol can reduce the pores on the surface of the prepared decorative material, enhance its compactness, reduce water permeability, and increase the hardness of the resin material, thereby increasing the hardness of the low-carbon weather-resistant decorative material.

[0085] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention, and are not used to limit the present invention.

[0086] In the following examples, the engineering waste soil includes red soil (engineering waste) and pottery clay (engineering waste), both of which are engineering waste from a certain place in Longgang District, Shenzhen, and are directly taken, crushed, ball-milled, and passed through a 200-mesh square hole sieve to obtain;

[0087] The acid-modified mineral powder is obtained by acidifying the mineral powder with oxalic acid;

[0088] The corundum was purchased from Chaoyue Filter Material Factory in Gongyi City, with a particle size of 60 mesh; the quartz powder was purchased from Runjia Quartz Sand Factory, with a particle size of 400 mesh; the sericite was purchased from Henan Borun Casting Materials Co., Ltd., with a particle size of 600 mesh; the silicon micropowder was purchased from Shanghai Chenqi Chemical Technology Co., Ltd., with a particle size of 1350 mesh; the wollastonite was purchased from Shanghai Chenqi Chemical Technology Co., Ltd.;

[0089] The coupling agent is KH-560, purchased from Nanjing Chuangshi Chemical;

[0090] The polyurethane is F0410, purchased from Shenzhen Jitian Chemical;

[0091] The acrylic emulsion is industrial grade and was purchased from Dongguan Taikang Polymer Technology Co., Ltd.

[0092] The ethylene-vinyl acetate copolymer emulsion (EVA emulsion) is 920, purchased from Wacker Chemical (China) Co., Ltd.;

[0093] The curing agent is polycarbodiimide, purchased from Norwick Chemical;

[0094] The nano aluminum sol is 80 nanometers and was purchased from Dezhou Jinghuo Technology Glass Co., Ltd.

[0095] The fiber is glass fiber purchased from Changsha Ningxiang Building Materials Co., Ltd.

[0096] The resin is a polymer resin, an epoxy resin, purchased from Huizhou Shengshida Technology Co., Ltd.

[0097] The thickener is hydroxyethyl methylcellulose, purchased from Qimeng Chemical;

[0098] The dispersant is SN5040, purchased from San Nopco;

[0099] The defoamer is ZJ-800, purchased from Guangzhou Zhijing Chemical Technology Co., Ltd.

[0100] Example 1

[0101] A low-carbon weather-resistant decorative material comprises the following raw materials in parts by mass: 100 parts of microwave-modified engineering waste soil (the engineering waste soil comprises 40 parts of laterite and 60 parts of pottery clay), acid-modified mineral powder (50 parts of corundum + 100 parts of quartz powder + 10 parts of sericite + 30 parts of wollastonite modified with aluminum silicate + 50 parts of silicon micropowder + 2 parts of oxalic acid), 7 parts of coupling agent, 10.5 parts of polyurethane emulsion, 42 parts of acrylic emulsion, 8 parts of fiber, 4 parts of curing agent and 50 parts of water.

[0102] Example 2

[0103] Compared with Example 1, the difference is that the amount of raw materials used is different. Please refer to Table 1 for the specific weight fractions of each raw material.

[0104] Example 3

[0105] Compared with Example 1, the difference is that the amount of raw materials used is different. Please refer to Table 1 for the specific weight fractions of each raw material.

[0106] Example 4

[0107] Compared with Example 1, the difference is that the amount of raw materials used is different. Please refer to Table 1 for the specific weight fractions of each raw material.

[0108] Example 5

[0109] Compared with Example 1, the difference is that the amount of raw materials used is different. Please refer to Table 1 for the specific weight fractions of each raw material.

[0110] Table 1 Mass fraction of each raw material in Examples 1-5

[0111]

[0112]

[0113] Comparative Example 1

[0114] Compared with Example 1, the difference is that unmodified wollastonite is used instead of wollastonite modified with aluminum silicate. Please refer to Table 2 for the specific mass fractions of each raw material.

[0115] Comparative Example 2

[0116] Compared with Example 1, the difference is that the mineral powder (corundum, quartz powder, sericite, wollastonite modified with aluminum silicate and silica powder) is not acidified with oxalic acid. Please refer to Table 2 for the specific mass fractions of each raw material.

[0117] Comparative Example 3

[0118] Compared with Example 1, the difference is that the amount of polyurethane emulsion used is 0. Please refer to Table 2 for the specific mass fractions of each raw material.

[0119] Comparative Example 4

[0120] Compared with Example 1, the difference is that the amount of acrylic emulsion is 0, the amount of EVA emulsion is 0, and the specific mass fractions of each raw material are shown in Table 2.

[0121] Comparative Example 5

[0122] Compared with Example 1, the difference is that the amount of mineral powder (corundum, quartz powder, sericite, wollastonite modified with aluminum silicate and silicon powder) is 0. Please refer to Table 2 for the specific mass fractions of each raw material.

[0123] Table 2 Mass fractions of each raw material in comparative examples 1-5

[0124]

[0125]

[0126] Example 6

[0127] A method for preparing a low-carbon weather-resistant decorative material comprises the following steps:

[0128] (1) Pour 50 parts of wollastonite powder into water, stir at a speed of 400 r / min, and after stirring into a uniformly dispersed suspension, test the pH value and adjust the pH value to 7 with ammonia water, heat in a water bath, and when the temperature rises to 80° C., add 0.5 parts of aluminum sulfate and 0.8 parts of sodium silicate solution, continue stirring for 30 minutes after the addition is complete to react, then filter, wash, filter again, dry in an oven at 105° C., and then break up to obtain a powder, and fully mix the obtained powder with 0.5 parts of a modifier silane coupling agent to obtain aluminum silicate-modified wollastonite;

[0129] (2) 100 parts of engineering waste soil (40 parts of laterite + 60 parts of pottery clay) were subjected to microwave treatment to obtain microwave-modified engineering waste soil; 50 parts of corundum, 100 parts of quartz powder, 50 parts of wollastonite modified with aluminum silicate and 2 parts of oxalic acid were mixed to obtain acid-modified mineral powder; wherein the microwave treatment parameter was 750W for 5 minutes;

[0130] (3) mixing the microwave-modified engineering spoil obtained in step (2) and the acid-modified mineral powder with 30 parts of water to obtain a mixture;

[0131] (4) adding 2 parts of coupling agent to the mixture, heating at 80° C., stirring and modifying the mixture to obtain a modified mixture;

[0132] (5) slowly adding 2 parts of thickener, 2 parts of dispersant, and 2 parts of defoamer to water in sequence, stirring at a medium speed (500 rpm) for 20 min, and then dispersing at a high speed (1000 rpm) for 20 min to obtain a first mixture, and then reducing the speed to 200 rpm and adding 20 parts of polyurethane emulsion, 40 parts of acrylic emulsion, the modified mixture of step (4), 0.5 parts of curing agent and 2 parts of fiber to the first mixture, stirring to obtain a slurry;

[0133] (6) Pour the slurry into a mold, dry it at 80° C., and demould it to obtain a low-carbon weather-resistant decorative material.

[0134] Example 7

[0135] A method for preparing a low-carbon weather-resistant decorative material comprises the following steps:

[0136] (1) 100 parts of engineering waste soil (40 parts of laterite + 60 parts of pottery clay) were subjected to microwave treatment to obtain microwave-modified engineering waste soil; 50 parts of corundum, 100 parts of quartz powder, 50 parts of wollastonite modified with aluminum silicate and 2 parts of oxalic acid were mixed to obtain acid-modified mineral powder; wherein the microwave treatment parameter was 750W for 5 minutes;

[0137] (2) mixing the microwave-modified engineering spoil and the acid-modified mineral powder obtained in step (1) with 30 parts of water to obtain a mixture;

[0138] (3) adding 3 parts of coupling agent to the mixture, heating and stirring at 100° C. to obtain a modified mixture;

[0139] (4) slowly adding 10 parts of polyurethane emulsion, 20 parts of acrylic emulsion, 5 parts of resin, 0.1 parts of thickener, 0.1 parts of dispersant, 0.1 parts of defoamer, 0.1 parts of curing agent and 2 parts of fiber to water in sequence, stirring at medium speed (300 rpm) for 15 minutes, and then dispersing at high speed (800 rpm) for 20 minutes to obtain a second mixture, and then reducing the speed to 100 rpm and adding the second mixture to the modified mixture of step (4), stirring to obtain a slurry;

[0140] (5) Pour the slurry into a mold, dry it at 70° C., and demould it to obtain a low-carbon weather-resistant decorative material.

[0141] Example 8

[0142] A method for preparing a low-carbon weather-resistant decorative material comprises the following steps:

[0143] (1) 100 parts of engineering waste soil (40 parts of laterite + 60 parts of pottery clay) were subjected to microwave treatment to obtain microwave-modified engineering waste soil; 50 parts of corundum, 50 parts of quartz powder, 70 parts of wollastonite modified with aluminum silicate and 2 parts of oxalic acid were mixed to obtain acid-modified mineral powder; wherein the microwave treatment parameter was 750W for 3 minutes;

[0144] (2) mixing the microwave-modified engineering spoil and the acid-modified mineral powder obtained in step (1) with 30 parts of water to obtain a mixture;

[0145] (3) adding 4 parts of coupling agent to the mixture, heating and stirring at 100° C. to obtain a modified mixture;

[0146] (4) slowly adding 10 parts of polyurethane emulsion, 40 parts of acrylic emulsion, 5 parts of aluminum sol, 5 parts of resin, 0.1 parts of thickener, 0.1 parts of dispersant, 0.1 parts of defoamer, 0.1 parts of curing agent and 1 part of fiber to water in sequence, stirring at medium speed (300 rpm) for 10 minutes, and then dispersing at high speed (800 rpm) for 20 minutes to obtain a third mixture, and then reducing the speed to 200 rpm and adding the third mixture to the modified mixture of step (4), stirring to obtain a slurry;

[0147] (5) Pour the slurry into a mold, dry it at 90° C., and demould it to obtain a low-carbon weather-resistant decorative material.

[0148] Performance Testing

[0149] The apparent relative density, wear resistance (load 5N), water absorption, contact angle, weather resistance and flame retardancy of the low-carbon weather-resistant decorative materials of Examples 1-8 and Comparative Examples 1-5 were tested, and the test results are shown in Table 3. The test method is as follows:

[0150] Apparent relative density: Tested in accordance with GB / T3810.3-2016;

[0151] Wear resistance (load 5N): Tested in accordance with GB / T9867-2008;

[0152] Water absorption rate: Tested in accordance with GB / T3810.3-2016;

[0153] Contact angle: measured by surface contact angle tester;

[0154] Weather resistance: Refer to international standard ASTM D4587;

[0155] Flame retardancy: refer to GB / T 14833-2020.

[0156] Table 3 Performance tests of Examples 1-8 and Comparative Examples 1-5

[0157]

[0158]

[0159] As can be seen from Table 3, the weather resistance test results of the low-carbon weather-resistant decorative materials of Examples 1-8 are better than those of Comparative Examples 1-5, indicating that the technical solution of the present application can improve the weather resistance of the material. It can also be seen from Table 3 that the wear resistance and water absorption test results of the low-carbon weather-resistant decorative materials of Examples 1-8 are also better than those of Comparative Examples 1-5, indicating that the technical solution of the present application can improve the wear resistance of the prepared decorative materials and reduce the water absorption, which is conducive to improving the stability and durability of the low-carbon weather-resistant decorative materials in a humid environment. Among them, since the wollastonite in Comparative Example 1 was not modified, the stability of the inorganic-organic macromolecular structure deteriorated, resulting in poor weather resistance; since the mineral powder in Comparative Example 2 was not acidified with oxalic acid, the stability of the inorganic-organic macromolecular structure deteriorated, resulting in poor weather resistance; since the first emulsion and the second emulsion were not used at the same time in Comparative Examples 3 and 4, the stability of the inorganic-organic macromolecular structure deteriorated, resulting in poor weather resistance; since Comparative Example 5 did not use mineral powder and only used construction waste soil, it was difficult to form a stable inorganic-organic macromolecular structure, and both weather resistance and wear resistance deteriorated.

[0160] The above description is only an exemplary embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the technical concept of the present invention, or direct / indirect application in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A low-carbon weather-resistant decorative material, characterized in that: The method comprises the following raw materials in parts by weight: 100 parts of microwave-treated engineering waste soil, 50-300 parts of acid-modified mineral powder, 2-8 parts of coupling agent, 10-25 parts of first emulsion, 20-70 parts of second emulsion, 2-16 parts of fiber, and 0.1-4 parts of curing agent; Wherein, the mineral powder comprises wollastonite modified with aluminum silicate; The first emulsion includes a polyurethane emulsion; The second emulsion includes at least one of vinyl acetate emulsion, pure acrylic emulsion, ethylene-vinyl acetate copolymer emulsion, styrene acrylic emulsion and vinyl acetate emulsion.

2. The low-carbon weather-resistant decorative material according to claim 1, characterized in that: The acid in the acid-modified mineral powder includes at least one of oxalic acid, carbonic acid, hydrochloric acid and nitric acid; and / or, The wollastonite modified with aluminum silicate is prepared by adding aluminum sulfate, sodium silicate, stearic acid and a titanate coupling agent to wollastonite; and / or, The mineral powder further comprises at least one of corundum, quartz powder, sericite and silicon powder, and the mass fraction of wollastonite modified with aluminum silicate in the mineral powder is 10-20%; and / or, The coupling agent includes at least one of a methacryloyloxyalkyl coupling agent, an epoxyhydroxyl coupling agent and an aminohydroxyl coupling agent; and / or, The fiber comprises at least one of glass fiber, carbon fiber, brucite fiber and wollastonite fiber; and / or, The curing agent includes any one of a polyamide curing agent, an aziridine curing agent and a polycarbodiimide curing agent.

3. The low-carbon weather-resistant decorative material according to claim 1, characterized in that: The low-carbon weather-resistant decorative material further comprises 5 to 20 parts of resin, wherein the resin comprises at least one of phenolic resin, epoxy resin, bismaleimide resin, cyanate resin and polyimide resin.

4. The low-carbon weather-resistant decorative material according to claim 1, characterized in that: The low-carbon weather-resistant decorative material also includes 1.5 to 5 parts of aluminum sol.

5. A method for preparing a low-carbon weather-resistant decorative material according to any one of claims 1 to 4, characterized in that: The following steps are involved: S10, mixing the microwave-treated engineering waste soil, acid-modified mineral powder and water to obtain a mixture; S20, mixing the mixture and the coupling agent, and heating to obtain a modified mixture; S30, mixing the modified mixture, the first emulsion, the second emulsion, the fiber and the curing agent to obtain a slurry; S40, pouring the slurry into a mold, drying, and demoulding to obtain the low-carbon weather-resistant decorative material.

6. The method for preparing a low-carbon weather-resistant decorative material according to claim 5, characterized in that: Before step S10, the method includes: Performing microwave treatment on engineering waste to obtain microwave-treated engineering waste; mixing mineral powder and acid to obtain acid-modified mineral powder; Wherein, the mass ratio of the mineral powder to the acid is (50-300):(1-5).

7. The method for preparing a low-carbon weather-resistant decorative material according to claim 5, characterized in that: In step S20, the heating temperature is 60-100° C.; and / or, In step S40, the drying temperature is 60-130°C.

8. The method for preparing a low-carbon weather-resistant decorative material according to claim 5, characterized in that: The step S30 comprises: mixing water and an auxiliary agent to obtain a first mixture; The first emulsion, the second emulsion, the modified mixed material, the fiber and the curing agent are added to the first mixture to obtain a slurry.

9. The method for preparing a low-carbon weather-resistant decorative material according to claim 5, characterized in that: The step S30 comprises: Mixing the first emulsion, the second emulsion, the resin, water, the additive, the fiber and the curing agent to obtain a second mixture; The second mixture is added to the modified mixture to obtain a slurry.

10. The method for preparing a low-carbon weather-resistant decorative material according to claim 5, characterized in that: The step S30 comprises: The first emulsion, the second emulsion, the aluminum sol, water, an additive, fibers and a curing agent are mixed to obtain a third mixture; The third mixture is added to the modified mixture to obtain a slurry.